2020
DOI: 10.29121/ijetmr.v7.i10.2020.755
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Relationship Between Multiple Intelligences of Higher Degree Students on Academic Performance in the University of Ibadan

Abstract: Research into investigation of the relationship between multiple intelligences of learners and academic performance is germane. This study investigated relationship between multiple intelligences of higher degree students and academic performance. Two research questions and three hypotheses guided the correlational study. Three hundred and thirty Master degree students of the University of Ibadan who are randomly selected made the sample. Three validated instruments: Simple Multiple Intelligence Inventory deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Numerous studies have looked at and demonstrated a link between students' multiple intelligence and emotional intelligence and their academic achievement, notably in English (Ayesha & Khurshid, 2013;Babantunde & Ayoola, 2020;Chew et al, 2013;Hernandez, 2019;Meher, 2021;Novelo, 2019;Yahaya et al, 2012). Naderi et al (2012) contended that, principally in support of multiple intelligence, some psychologists observed a connection between academic success and multiple intelligence and claimed a cause-and-effect relationship between the two variables.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have looked at and demonstrated a link between students' multiple intelligence and emotional intelligence and their academic achievement, notably in English (Ayesha & Khurshid, 2013;Babantunde & Ayoola, 2020;Chew et al, 2013;Hernandez, 2019;Meher, 2021;Novelo, 2019;Yahaya et al, 2012). Naderi et al (2012) contended that, principally in support of multiple intelligence, some psychologists observed a connection between academic success and multiple intelligence and claimed a cause-and-effect relationship between the two variables.…”
Section: Introductionmentioning
confidence: 99%